Bacterial regrowth in water reclamation and distribution systems revealed by viable bacterial detection assays. (February 2016) - Lin, Yi-wen; Li, Dan; Gu, April Z.; Zeng, Si-yu; He, Miao
Abstract: Microbial regrowth needs to be managed during water reclamation and distribution. The aim of present study was to investigate the removal and regrowth of Escherichia coli ( E. coli ) and Salmonella in water reclamation and distribution system by using membrane integrity assay (PMA-qPCR), reverse transcriptional activity assay (Q-RT-PCR) and culture-based assay, and also to evaluate the relationships among bacterial regrowth, and environmental factors in the distribution system. The results showed that most of the water reclamation processes potentially induced bacteria into VBNC state. The culturable E. coli and Salmonella regrew 1.8 and 0.7 log10 in distribution system, which included reactivation of bacteria in the viable but non-culturable (VBNC) state and reproduction of culturable bacteria. The regrowth of culturable E. coli and Salmonella in the distribution system mainly depended on the residual chlorine levels, with correlations (R 2 ) of −0.598 and −0.660. The abundances of membrane integrity and reverse transcriptional activity bacteria in reclamation effluents had significant correlations with the culturable bacteria at the end point of the distribution system, demonstrating that PMA-qPCR and Q-RT-PCR are sensitive and accurate tools to determine and predict bacterial regrowth in water distribution systems. This study has improved our understanding of microbial removal and regrowth in reclaimed water treatment and distribution systems. And the results also recommended that more processes should be equipped to remove viable bacteria in water reclamation plants for the sake of inhibition microbial regrowth during water distribution and usages. Graphical abstract: Highlights: Reclaimed water treatment and disinfections can induce bacteria into a VBNC state. The regrowth of Salmonella was higher than that of Escherichia coli in the distribution system. The regrowth of E. coli mainly depended on the depletion of total chlorine. PMA-qPCR is recommended to predict bacterial regrowth in distribution systems.